Design for global markets : a user-value-based approach. - Boztepe, Suzan, ....- (Saarbrücken : VDM, 2009)
In a global economy, no company can safely assume that their products will be accepted in foreign markets. The main challenge is to understand and meet the latent needs of culturally diverse groups. This book examines from users' perspective the issue of developing new products for global markets. Given that the primary goal of any design is to create value for users, Boztepe argues that the concept of user value could be a driving force in design decision-making. Through interviews with women about their kitchen practices and observations of their use of kitchen appliances, she presents an ethnographic account of users' value assignment to everyday products as they interact with them. She also examines the cultural elements involved in the process of value assignment. Boztepe uses these findings to propose a user-value-based adaptation framework to assist marketers, product designers and managers in dealing with the complex issue of designing and tailoring products for local needs.